Analysis of the Influence of Artificial Intelligence (AI), Machine Learning, and Data Analytics on Marketing Performance at Technology Start-Ups in Jakarta - Muchamad Sobri Sungkar; Mukrodin Mukrodin; Muhamad Bakhar (Westscience Press, 2024)
The integration of advanced technologies such as Artificial Intelligence (AI), Machine Learning (ML), and Data Analytics has transformed marketing practices, especially in technology-driven sectors like start-ups. This study examines the influence of these technologies on marketing performance in technology start-ups in Jakarta using quantitative analysis. Data were collected from 150 respondents through a structured questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The findings reveal that AI, ML, and Data Analytics each have significant positive impacts on marketing performance, with Data Analytics emerging as the strongest individual predictor. Moreover, the combined use of these technologies demonstrates a synergistic effect, amplifying their overall influence. These results highlight the critical role of technology integration in enhancing marketing efficiency, customer engagement, and return on investment. The study contributes to the theoretical understanding of technology adoption in marketing and provides actionable insights for start-ups aiming to leverage these tools for competitive advantage.